Pacagoya Ritual Tradition as a Manifestation of Pancasila Values Character in Protecting the Natural Environment - Abd. Chaidir Marasabessy; Darto Wahidin; Setiawati Setiawati; Much. Hidayah Marasabessy (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
Pacagoya is imbued with symbols, meanings, and values. This qualitative phenomenological study investigates the significance of rituals within Kalaodis village, serving as a manifestation of Pancasila values that advocate for the protection of the natural environment. The research utilized a combination of interview data gathered from customary officials, as well as scientific journals, books, and pertinent documents. Value theory was employed for the analysis, leading to the reduction, presentation, and synthesis of data to uncover the meanings and values inherent in the rituals. The findings indicate that Pacagoya embodies ethical values through the principle of Bobeto, which serves as a guiding framework, reminding individuals of the importance of not acting arrogantly toward nature. This principle is further exemplified by the concept of Legu dou. Bobeto, which represents customary norms, expresses aspects of global diversity, whereas Marong reflects the spirit of mutual cooperation in the management of agricultural land. Pacagoya integrates the relationships between humans, nature, and the Creator, symbolizing a harmonious balance that aligns with the First Principle of Pancasila. Furthermore, the interactions among individuals, alongside their civic responsibilities to manage and protect their environment—particularly forests—underscore the values associated with the Second Principle of Pancasila. In this context, Bobeto exemplifies the responsiveness of the customary community and plays a vital role in social supervision, reflecting the Third Principle of Pancasila. The norms embodied in Bobeto are binding for the people of Tidore, illustrating the values inherent in the Fourth Principle of Pancasila by fostering awareness and accountability in decision-making processes concerning environmental protection. Additionally, Bobeto functions as a mechanism of self-regulation, promoting equilibrium between rights and responsibilities. Equitable treatment of the natural environment contributes to the welfare of the community, aligning with the values of the Fifth Principle of Pancasila. The mandate of Bobeto serves as a representation of prudent behavior, actualized in contemporary practices through the Pacagoya tradition, which conveys essential moral messages regarding environmental stewardship. This study offers significant theoretical and practical contributions by emphasizing the values of Bobeto and Marong within the context of the Pacagoya ritual, thereby highlighting the necessity of integrating these values into various dimensions of life, particularly in the development of social values and the enhancement of the Pancasila Student Profile.